2020
DOI: 10.1021/acs.jcim.0c00329
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study of Membrane Lipid Composition Regulating Conformation and Hydration of Influenza Virus B M2 Channel

Abstract: The proton conduction of transmembrane influenza virus B M2 (BM2) proton channel is possibly mediated by the membrane environment, but the detailed molecular mechanism is challenging to determine. In this work, how membrane lipid composition regulates the conformation and hydration of BM2 channel is elucidated in silico. The appearance of several important hydrogen-bond networks has been discovered, as the addition of negatively charged lipid palmitoyloleoyl phosphatidylglycerol (POPG) and cholesterol reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…These revealed that Phe5 tetrad of BM2 formed a larger outward-facing phenylene ring conformation than Val27 tetrad of AM2. Hence Phe5 could not block AMT from entering the BM2 channel pore, which is consistent with experimental findings , and our previous work …”
supporting
confidence: 93%
See 2 more Smart Citations
“…These revealed that Phe5 tetrad of BM2 formed a larger outward-facing phenylene ring conformation than Val27 tetrad of AM2. Hence Phe5 could not block AMT from entering the BM2 channel pore, which is consistent with experimental findings , and our previous work …”
supporting
confidence: 93%
“…Hence Phe5 could not block AMT from entering the BM2 channel pore, which is consistent with experimental findings 8,27 and our previous work. 12 Interestingly, we observed that when AMT adopted the up binding mode bound to BM2 channel, the free-energy barrier was smaller than the down binding mode (Figure S2). The smaller energy barrier suggested AMT might favor the up binding mode in the BM2 channel pore.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…His53, His62, His185, His208, His224, His290, His378, His388, His416, His501, and His506 were protonated at ε nitrogen atom. As we know, CYP is a kind of membrane protein, and previous research has found that the membrane environment is essential for the function of membrane proteins. , The influence of the membrane environment is reflected in the structural changes during the simulation. For CYP1A2, the existing membrane environment could help stabilize the secondary structures (A′ helix, B-C loop, F-G loop, and so on).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, CYP1A2 is a structurally conserved transmembrane protein like other CYPs. As a membrane protein, the existence of a membrane environment is essential for the function of CYP1A2, according to our previous work. , The transmembrane segment of membrane proteins is hard to determined, and only the cytoplasmic structure of CYP1A2 was identified successfully by Johnson et al …”
Section: Introductionmentioning
confidence: 99%